TEXTILE PRODUCTION AND CONSUMPTION IN ROMAN PROVINCES AND IN FREE GERMANIA – A 21 ST CENTURY PERSPECTIVE - Kaczmarek, Zofia (My University, 2017)
The paper aims to present the state of research on Roman Period archaeological textiles and new, 21 st century perspectives for further analyses. The textiles proves to be important from the viewpoint of provincial economy, trade and cultural exchange. That is why, a special emphasis is put on the textile types, which are called Roman imports.
Keywords: Tkaniny archeologiczne; Importy rzymskie